3x - 4 + 1 = -2x - 5 + 5x
First, simplify 3x - 4 + 1 to 3x - 3. / Your problem should look like: 3x - 3 = -3x - 5 + 5x
Second, simplify -2x - 5 + 5x to 3x - 5. / Your problem should look like: 3x - 3 = 3x - 5
Third, cancel 3x on both sides. / Your problem should look like: -3 = -5
Fourth, since -3 = -5 is false, there is no solution.
Answer: No solution
Answer:
Could be C) or D) None of these, 29688.05cm^2
Step-by-step explanation:
Did the question to round off to any numbers?
Formula for cylinder's T.S.A: 2 π r h + 2 π r^2
Diameter= 2 x radius
Radius = 70cm / 2 = 35cm
Height -> need to convert m to cm -> 100cm
Substitute these values into the formula:
2 x π x 35 x 100 + 2 x π x (35)^2 = 29688.05cm^2
Answer:
8 units
Step-by-step explanation:
The longer leg extends upward from y = -3 to y = 5, so its length is 8 units.
Answer:
y= -1x - 6
I really hope this helps you!